if cos inverse x minus cos inverse x =0 write down the value of x
Answers
Answered by
1
Proof:
Let, cos−1 x = α and cos−1 y = β
From cos−1 x = α we get,
x = cos α
and from cos−1 y = β we get,
y = cos β
Now, cos (α - β) = cos α cos β + sin α sin β
⇒ cos (α - β) = cos α cos β + 1−cos2α−−−−−−−−√ 1−cos2β−−−−−−−−√
⇒ cos (α - β) = (xy + 1−x2−−−−−√1−y2−−−−−√)
⇒ α - β = cos−1(xy + 1−x2−−−−−√1−y2−−−−−√)
or, cos−1 x - cos−1 y = cos−1(xy + 1−x2−−−−−√1−y2−−−−−√)
Therefore, arccos(x) - arccos(y) = arccos(xy) + 1−x2−−−−−√1−y2−−−−−√) Proved.
HOPE IT HELPS YOU
MARK IT AS BRAINLIEST
Similar questions